Adipose mesenchymal stem cell-derived antioxidative extracellular vesicles exhibit anti-oxidative stress and immunomodulatory effects under PM2.5 exposure. (15th January 2021) - Gao, Yongheng; Huang, Xia; Lin, Hongwei; Zhao, Mingxuan; Liu, Wei; Li, Wangping; Han, Luyao; Ma, Qiong; Dong, Chuan; Li, Yujuan; Hu, Ying; Jin, Faguang
Graphical abstract: Abstract: PM2.5 exposure elevates the level of reactive oxygen species (ROS) in the lungs and leads to lung injury or other pulmonary conditions. Nrf2 is a key antioxidative regulator that suppresses ROS production. Extracellular vesicles (EVs) secreted by adipose mesenchymal stem cells (ADSCs) have been identified as therapeutic as well as potential drug/gene/protein carriers. In this study, we established rat (PM2.5, 100 μL, 5 mg/mL) or cell (PM2.5, 50 μg/mL) models to conduct in vivo and in vitro studies on the adverse pulmonary effects of PM2.5 . Our findings indicated that the initial responses to PM2.5 exposure were robust oxidative stress and inflammation. EVs and antioxidative EVs (Antioxi-EVs, derived from ADSCs that overexpress Nrf2) had been tested as interventions in PM2.5 -treated rat or cell models through tracheal instillation or co-incubation. Treatment with EVs or Antioxi-EVs (3 × 10 10 particles in vivo and 1 × 10 9 in vitro ) was found to have a suppressive effect on the levels of ROS and inflammatory cytokines, with Antioxi-EVs having a superior effect on anti-oxidative stress. In particular, the occurrence of lung injury or cell apoptosis correlated positively with the ROS level, and inhibition of ROS by upregulating Nrf2 alleviated lung injury and cell apoptosis. Furthermore, treatment with EVs or Antioxi-EVs increased the level of M2-like macrophages as compared to treatment with PBS and further reduced IL-6 and TNF-α levels. Our results suggest that Antioxi-EVs can reduce the severity of oxidative stress, inflammation, and lung injury induced by PM2.5 via anti-oxidative stress and immunomodulation pathways.